Prospective study of fine needle aspiration cytology of clinically palpable breast lump with histopathological correlation - Hebbar, Ashwin K.; Iyanna, Harish (International Journal of Research in Medical Sciences, 2017)
Background and objectives: This study was conducted to compare the diagnostic accuracy of fine needle aspiration cytology in differentiating the benign and malignant lesions of palpable breast lump with histopathological correlation and also to study the accuracy of the needle tip localizing the tumor during fine needle aspiration cytology procedure. Methods: Two years prospective study was conducted in our institution and in that 100 patients underwent fine needle aspiration cytology of the palpable breast lump after thorough physical examination. The cytological diagnosis was classified in to 3 groups benign, suspicious and malignant. After this reporting all the patients were later subjected to open/excision biopsy and its histopathological confirmation. Later diagnostic accuracy of cytology reporting was compared with that of histopathology. Accuracy of the needle tip in localizing the tumor in fine needle aspiration cytology was also studied by comparing the normal glandular cell aspirate with tumor cell aspirate. Repeat cytology was carried out before open/excision biopsy if the pathologist reports the cytology slide as “inadequate”. Results: We had accuracy rate of 100% for benign lesion and 93.10% for malignant lesion with false negative rate of 6.9% and false positive rate of zero with fine needle aspiration cytology in the diagnosis of palpable breast lump. The overall sensitivity of fine needle aspiration in diagnosing the palpable breast lump is 93.10%, specificity is 100%, positive predictive value is 100% and negative predictive value is 90.47%. Since inadequate sampling rate is 2% in our study, the accuracy rate of needle tip in localizing the tumor in fine needle aspiration cytology is 98%. Conclusion: Since our diagnostic accuracy rate and predictive values are very high and comparable to any other published series it can be advised that the patients in which fine needle aspiration cytology is unequivocally diagnostic for cancer can be managed directly by mastectomy (or any other definitive therapy). A diagnosis of suspicious for cancer must be confirmed by an open biopsy or intraoperative frozen section or rapid hemotoxyline and eosine staining (depending on availability). Since the accuracy of the needle tip in localizing the lump is very high (98%), the diagnostic accuracy of fine needle aspiration cytology can be increased by performing repeat aspiration on the lump for which previously being reported as inadequate or unsatisfactory sampling before advising for open biopsy.